Modulation of Brain-Derived Neurotrophic Factor (BDNF)-Induced Trophic Signalling as an Alternative Treatment for Alzheimer’s Disease - -, Muthmainah (Cermin Dunia Kedokteran, 2015)
Alzheimerâ€™s disease (AD) is a disorder of synaptic function and neuronal degeneration characterised by decline in memory and cognition as well as changes of personality. Brain-Derived Neurotrophic Factor (BDNF) is a major modulator of synaptic plasticity and is an acknowledged pharmacological target for the treatment of a range of neurological disorders including AD. Attempts to supply BDNF exogenously are limited by side effects. An alternative strategy to enhance BDNF-induced trophic signalling is through amplification of neural response to the reduced supply of endogenous BDNF found in AD.Penyakit Alzheimer adalah kelainan fungsi sinaptik dan degenerasi neuron yang ditandai oleh penurunan fungsi kognitif dan memori serta perubahan kepribadian. Brain-Derived Neurotrophic Factor (BDNF) adalah modulator plastisitas sinaptik utama dan telah diakui merupakan sasaran pengobatan berbagai kelainan neurologis termasuk penyakit Alzheimer. Usaha memberikan BDNF eksogen terkendala oleh berbagai efek samping. Alternatif lain meningkatkan signal trofik BDNF adalah dengan amplifikasi respons saraf terhadap terbatasnya kadar BDNF yang sering dijumpai pada penyakit Alzheimer.Â